PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KINERJA KARYAWAN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT. Pos Indonesia Kota Madiun) - Nurmalia Ariarni; Tri Wulida Afrianty (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
The aim of this research is to analyze the influence of perceived organizational support (POS) on employee performance mediated by employee engagement. The respondents of this research were 62 employees of PT. Pos Indonesia Madiun City. To test the hypotheses, a hierarchical regression analysis was conducted using SPSS version 21. The result showed that 1) there was a positive effect of perceived organizational support on employee engagement 2) there was a positive effect of perceived organizational support on employee performance 3) there was a positive effect of employee engagement on employee performance. In addition, 4) employee engagement was confirmed as a mediating variable on the effect of perceived organizational support on employee performance in PT. Pos Indonesia Madiun City. Key words : perceived organizational support (POS), employee engagement, employee performance. ABSTRAK Tujuan penelitian ini adalah untuk menganalisis pengaruh perceived organizational support (POS) terhadap kinerja karyawan yang dimediasi oleh employee engagement. Responden dalam penelitian ini adalah 62 karyawan PT. Pos Indonesia Kota Madiun. Untuk menguji hipotesis menggunakan hierarchial regression analysis dengan bantuan SPSS versi 21. Hasil penelitian ini menunjukkan bahwa: 1) terdapat pengaruh positif perceived organizational support terhadap employee engagement 2) terdapat pengaruh positif perceived organizational support terhadap kinerja karyawan, 3) terdapat pengaruh positif employee engagement terhadap kinerja karyawan. Selain itu 4) employee engagement terbukti sebagai variabel mediasi pada pengaruh perceived organizational support terhadap kinerja karyawan di PT. Pos Indonesia Kota Madiun. Kata Kunci: perceived organizational support (POS), employee engagement, kinerja karyawan.